EFFECT OF BOTANICAL DENSITIES IN YIELD AND GROWTH CHARACTERS FOR SOME SUNFLOWER (Helianthus annuus L.) CULTIVERS (Mesopotamia Journal of Agriculture)
Sunflower crop sowed with densities of distance between plants (25,30, 35,40 cm) for three varieties Mangarin, Azur and Locc carried out with the factorial experiment in Randomized Complete Block Design (RCBD) in the field of Agricultural Technical College Alrashidia - Mosul at autumn season 2011 to study it's effect on growth and yield. The results showed that the variety Azur had a good performance for plant height, individual plant seeds yield and total seeds yield characters, the distance 25cm between plants were which achieved an increase in plant height, stem diameter and total seeds yield, a decrease in the average of characteristics when increasing the distance between the plants was shown, The interaction between Locc variety and distance 25cm between plants was higher in total seeds yield .